An empirical study on grammatical error uttered by non-native English students - I Wayan Eka Dian Rahmanu; Ida Bagus Gde Nova Winarta; Ni Putu Wiwiek Ary Susyarini (English, 2020)
This research was conducted to analyze students’ error grammatical uttered by 20 El. Tourism Trainee students. To data collection done through observation, aided by audio recording and it was completed by the note-taking technique during the research. The data were analyzed descriptively and qualitatively using classroom research. The data collected by recording the students’ conversation was done teaching and learning activity in the classroom. The results of the analysis were found that students ignore the rule of an interrogative in asking a question. Most of the students tended to obtain dubious in expressing the statement and question during the conversation. The conclusion the students’ ignorances because of their knowledge of the grammatical structure they are learning and practising during their activity of doing their tasks.